Descrição anátomo-topográfica do coração da paca (Agouti paca) - Pinheiro Avila, Bruna Helena [UNESP]; Fernandes Machado, Marcia Rita [UNESP]; de Oliveira, Fabricio Singaretti (Universidade Federal do Rio Grande do Sul (UFRGS), 2010)
Background: The domestic animals heart is a conical hollow viscera, surrounded by pericardium, laterally compressed, accompanying the thorax shape. Atriums constituted the heart basis and their auricles partially bound the initial portion of the aorta and pulmonary trunk. In mammals, heart is kept suspended in the thoracic cavity and the pericardic sac is fixed dorsally by great veins and arteries roots, and ventrally fixed to the sternum, although its fixation to the diaphragm varies among species. This paper aimed to describe morphological aspects of the heart of the paca, the second biggest Brazilian rodent.Materials, Methods & Results: There were used 12 hearts of adult pacas for this study, obtained from the UNESP, Jaboticabal, SP, which died due fights or anesthesia during bandages or radiograph exams. The thoracic aorta was filled with colored latex and the animal was set in a 10% formaldehyde solution for at least 72 hours. The thoracic cavity was dissected and hearts individualized and measured with a paquimeter, lateromedially, craniocaudally and dorsoventrally. The paca heart is placed between the first and fifth intercostal space (ICS), in a craniocaudal oblique position; its basis is craniodorsally positioned, on the middle third between the first and second ICS and its apex is located near the sternodiaphragmatic joint, on the fifth ICS, tilted to the left antimere. The heart is surrounded by pericardium, which from ventrocaudally is originated the sternopericardic ligament, that continues as phrenopericardic ligament. At the heart basis, the rising of the pulmonary trunk was observed and the conus arteriosus formed a typical projection. The aorta also rised from the heart basis and its arch, which was caudally curved, crossed dorsally the pulmonary trunk; the right cranial and caudal cava veins drained to the right atrium. There is a left cranial cava vein, which surrounded the left atrium and joined the right caudal cava vein on the right atrium. The azygos vein joins the right cranial cava vein and four pulmonary veins drained to the left atrium. At palpation, a hard structure on the rising of the aorta was observed, similarly to a cartilaginous tissue, which would be part of the cardiac skeleton. The left and right coronary arteries were observed in all hearts.Discussion: The paca heart is anatomica and topographically similar to those of domestic mammals, differing from them for being placed one intercostal space more cranial and due to the presence of two cranial cava veins, the left and the right ones, besides the presence of the caudal cava vein. This vascular description is similar to that of small rodents, as rats and mice. In paca heart, the sinus venous, the terminal crest, the oval fossa, the atrioventricular valvae, the papillary muscles and tendinous cords, besides smooth atriums and auricles covered by pectinate muscles, were observed. The sternopericardic ligament, which is dorsally elongated as phrenopericardic ligament, is similar to the one present in humans, pigs, castors, and different from the one observed in carnivorous, that presents the phrenopericardic ligament and from the one of horses and ruminants, which present the sternopericardic ligament.
Anatomotopographic description of the paca heart (Agouti paca)
Keywords: anatomy; heart; Agouti paca